The major leaf ferredoxin Fd2 regulates plant innate immunity in Arabidopsis. (26th December 2017) - Wang, Mo; Rui, Lu; Yan, Haojie; Shi, Hua; Zhao, Wanying; Lin, Jinshan Ella; Zhang, Kai; Blakeslee, Joshua J.; Mackey, David; Tang, Dingzhong; Wei, Zhongmin; Wang, Guo‐Liang
Summary: Ferredoxins, the major distributors for electrons to various acceptor systems in plastids, contribute to redox regulation and antioxidant defence in plants. However, their function in plant immunity is not fully understood. In this study, we show that the expression of the major leaf ferredoxin gene Fd2 is suppressed by Pseudomonas syringae pv. tomato ( Pst ) DC3000 infection, and that knockout of Fd2 ( Fd2‐KO ) in Arabidopsis increases the plant's susceptibility to both Pst DC3000 and Golovinomyces cichoracearum . On Pst DC3000 infection, the Fd2‐KO mutant accumulates increased levels of jasmonic acid and displays compromised salicylic acid‐related immune responses. Fd2‐KO also shows defects in the accumulation of reactive oxygen species induced by pathogen‐associated molecular pattern‐triggered immunity. However, Fd2‐KO shows enhanced R‐protein‐mediated resistance to Pst DC3000/ AvrRpt2 infection, suggesting that Fd2 plays a negative role in effector‐triggered immunity. Furthermore, Fd2 interacts with FIBRILLIN4 (FIB4), a harpin‐binding protein localized in chloroplasts. Interestingly, Fd2, but not FIB4, localizes to stromules that extend from chloroplasts. Taken together, our results demonstrate that Fd2 plays an important role in plant immunity.